METHOD FOR EARLY DIAGNOSIS OF MACROSOMIA - Баева, Ирина Юрьевна; Константинова, Ольга Дмитриевна; Каган, Илья Иосифович; Щетинина, Юлия Сергеевна (Mother and Baby in Kuzbass, 2023)
The aim of the research – working-out and clinical approbation of a method of early diagnosis of macrosomia. Material and methods. At the first stage the retrospective study was conducted of 3760 histories of term and delayed births that occurred in the city maternity hospital in Orenburg from January 1, 2010 to January 1, 2013. There were 376 birth histories of women who gave birth the children with a fetal weight of 4000 g or more, 3384 birth histories of women who gave birth the children with fetal weight of 3000-3999 g. At the second stage due to the cohort prospective study 500 pregnant women were analyzed who delivered term, singleton, live born infants for 2015-2020 years. The study population was divided into 2 groups according to the assessment fetal weight (with fetal weight 3000-3995 g, 4000 g and more). Fetometry included measurement of the biparietal head diameter, fronto-occipital diameter, head circumference, abdominal circumference, femur length according to the generally accepted method using the centile scales of M.V. Medvedev (2010) and F.P. Hadlock [10]. Results. The first time on the basis of ultrasound scan one of the patterns of the growth rate development of macrosomic fetus was established, which consists in the maximum magnification of the growth rate of their skeleton at 27-28 weeks of intrauterine development. The practical significance of the results of the study lies in the development and implementation of a new method for early prediction of the macrosomic fetuses. The method consists in calculating the percentage increase in the main ultrasound parameters of the fetus in the gestational age of 27-28 weeks in relation to the screening period of the second trimester of pregnancy, with their value of 20 % or more with a sensitivity of 89.1 % and a specificity of 93.5 %, it is possible to predict the development of a large fetus (OR 7.1; 95% CI 4.67 – 10.87). Conclusion. The growth rate of the skeleton of large fetuses represented by ultrasonic parameters significantly increases at 27-28 weeks of pregnancy and can be as a reliable sign for early diagnosis of macrosomia.